STRUKTUR KOMUNITAS HUTAN MANGROVE DI DESA BUDO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Sarifudin Tidore; Calvyn FA Sondak; Antonius P Rumengan; Erly Y Kaligis; Elvy Like Ginting; Christine Kondoy (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Mangrove forest can grow on the muddy soil, along the coast and around the river estuaries that are affected by the tidal. The mangrove forest has a specific vegetation structure. Study on the structure of the mangrove forest community, was carried out in the Budo Village. Mangrove community structure data was taken using line transect method. A 100 m line was established from the sea perpendicular to the coast. A total of three line transects was made and each line has five 10 x 10 m plots with 20 m distance between plots. Distance between transect is 50m. This study found that three mangrove species Rhizophora apiculata, Sonneratia alba, and Bruguiera gymmorrhiza were found in the three transects during this study. The highest species biodiversity index was found in transect two (Hâ€™ = 0.97). R. apiculata has the highest density and relative density 0.05 ind/m2 and 67.57%. Both R. apiculata and S. alba have the highest frequency and relative frequency of 1.00 and 50% respectively. The highest species coverage and relative coverage area is belonging to S. alba in transect two, 25,89 and 63.57%. S. alba has the highest Important value index 140.72 in transect two.Keywords: Budo Village, Mangrove Forest, Community Structure.Â